Roboti [ science and systems IV - Brock, Oliver; Ramos, Fabio; Trinkle, Jeffrey C. (MIT Pres, 2009)
State-of-the-art robotics research on such topics as manipulation, motion planning, micro-robotics, distributed systems, autonomous navigation, and mapping.